Treating black women with eating disorders : a clinician's guide - Small, Charlynn; Fuller, Mazella (New York, NY : Routledge, 2020)
"The first of its kind, this edited volume provides in-depth, culturally sensitive material intended for addressing the unique concerns of black women with eating disorders in addition to comprehensive discussions and treatment guidelines for this population. The contributing authors - all of whom are black professionals providing direct care to black women - offer a range of perspectives to help readers understand the whole experience of their black female clients. This includes not only discussion of their clients' physical health but also of their emotional lives and the ways in which the stresses of racism, discrimination, trauma, and adverse childhood experiences can contribute to disordered eating. Through a wealth of diverse voices and stories, chapters boldly tackle issues such as stereotypes and acculturative stress. Clinicians of any race will gain new tools for assessing, diagnosing, and treating disordered eating in black women and will be empowered to provide better care for their clients"--
Only a Dog Wants a Bone! The Other End of the Eating Spectrum : Overweight and Obesity / Dawn McMillan -- The Presence of Black Women in Eating Disorders Treatment Facilities / Kena Watson -- The Weight of Shame : Black Women's Struggle with Binge Eating Disorder / Paula Edwards-Gayfield -- Food as a Drug : Mental Problem, Spiritual Solution / Joyce Woodson -- Creative Training Approaches for Clinicians-in-Training Working with African American Women with Eating Disorders / Jacqueline Conley -- Disordered Eating Habits of a Black Deaf Adolescent Female : A Case Study Applying a Cognitive Behavioral Therapy Approach to School Psychological Services / Erica Payne -- Food for Thought, Mind, and Body : Exploring Embodiment Techniques for Black Queer Women / Anisha Cooper -- Multidisciplinary Treatment Teams as Best Practice for Treating Eating Disorders and Body Image for College Students : Who Should Be at the Table? / Mary Churchill -- Evolution of the Fluffy Ideal in Jamaica / Venecia Pearce-Dunbar and Caryl James Bateman.
OCLC-licensed vendor bibliographic record.
Keywords: Eating disorders in women; PSYCHOLOGY / Psychopathology / Eating Disorders